MANAJEMEN KLINIK BACA DALAM MENSTIMULASI MINAT BACA SISWA DI MADRASAH - Muh. Hamzah; Fathor Rozi; Siti Khotimah (Autentik : Jurnal Pengembangan Pendidikan Dasar, 2022)
This study aims to analyze and examine the stimulation of reading culture with the 'reading clinic' program conducted in elementary schools. This research was conducted in elementary schools at MI Nurus Salam Kotaanyar Probolinggo. This research uses a qualitative approach. Data analysis techniques include data reduction, data display, and an overview or conclusion. The results showed that; first, the MI Nurus Salam institution uses a program called a 'reading clinic' to stimulate a reading culture for students; second, the presentation is done by knowing the program, implementing the reading clinic program, and evaluating the program. The implications obtained in the stimulation of reading culture in madrasas through the reading clinic game program are that students can develop reading comprehension and are more enthusiastic and enthusiastic about carrying out activities at the clinic with the creativity carried out by the teacher.